The Role of Artificial Intelligence in Modern Healthcare and Biomedical Innovation - Upadhyay, Ritesh; Mehta, Barkha; Mehta, Jigesh; V Metre, Anand; S Bhakhar, Mathurkumar (Journal of Innovations in Data Science and Big Data Management, 2025)
Medical science is going through a big change, thanks to the fast growth of artificial intelligence (AI). What was once just an idea is now a key tool in healthcare, changing how medical research is done, how treatments are given, and how patients are cared for. In this review, we look at how AI is affecting different areas of medicine, including drug development, surgery, biotechnology, and treatment options. AI’s impact on healthcare is wide and deep. It makes the process of finding new drugs more efficient and cost-effective, which could help bring life-saving medicines to patients faster. In surgery, AI tools are becoming more common, helping doctors perform better and improve patient results. In biotechnology, AI is helping understand complex genes, leading to personalized medicine and better drug production. Also, AI helps create new treatments that let doctors tailor care to each patient’s needs. In this review, we’ll look at how AI has evolved in medicine, what it is being used for today, and where it might go in the future. However, there are challenges to using AI in healthcare, like ethical issues, rules that need to be followed, and protecting patient information. Overall, combining AI with medicine is changing healthcare for the better, offering new ways to treat diseases, find illnesses early, and improve patient care. This review gives an overview of how cutting-edge technology and the goal of better health can work together.